Electrical coupling between hippocampal neurons: contrasting roles of principal cell gap junctions and interneuron gap junctions - Traub, Roger D.; Gutiérrez, Rafael; Draguhn, Andreas (Cell & tissue research, 2018)
There is considerable experimental evidence, anatomical and physiological, that gap junctions exist in the hippocampus. Electrical coupling through these gap junctions may be divided into three types: between principal neurons, between interneurons and at mixed chemical (glutamatergic)/electrical synapses. An approach, combining in vitro experimental with modeling techniques, sheds some light on the functional consequences of electrical coupling, for network oscillations and for seizures. Additionally, in vivo experiments, using mouse connexin knockouts, suggest that the presence of electrical coupling is important for optimal performance on selected behavioral tasks; however, the interpretation of such data, in cellular terms, has so far proven difficult. Given that invertebrate central pattern generators so often depend on both chemical and electrical synapses, our hypothesis is that hippocampus-mediated and -influenced behaviors will act likewise. Experiments, likely hard ones, will be required to test this intuition.
Gesehen am 16.05.2019